Athens & Jerusalem - Shestov, Lev, 1866-1938; Martin, Bernard, 1928-; Fotiade, Ramona (Athens, Ohio : Ohio University Press, 2016)
For more than two thousand years, philosophers and theologians have wrestled with the irreconcilable opposition between Greek rationality (Athens) and biblical revelation (Jerusalem).
Cover; Contents; Introduction to the Second Edition; Prefatory Note; Introduction; Foreword; I Parmenides in Chains; II In the Bull of Phalaris; III On the Philosophy of the Middle Ages; IV On the Second Dimension of Thought; Lev Shestov-Biographical Timeline; Notes; Bibliography; Index
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (EBSCO, viewed January 27, 2017).
Keywords: Religion -- Philosophy; Philosophy and religion; PHILOSOPHY / General; PHILOSOPHY / Movements / Phenomenology; PHILOSOPHY / Movements / General; Philosophy and religion; Religion -- Philosophy; RELIGION / Philosophy; Electronic books